2009
DOI: 10.1681/asn.2008121286
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Glutamatergic Signaling Contributes to the Function of the Glomerular Filtration Barrier

Abstract: Podocytes possess the complete machinery for glutamatergic signaling, raising the possibility that neuron-like signaling contributes to glomerular function. To test this, we studied mice and cells lacking Rab3A, a small GTPase that regulates glutamate exocytosis. In addition, we blocked the glutamate ionotropic N-methyl-D-aspartate receptor (NMDAR) with specific antagonists. In mice, the absence of Rab3A and blockade of NMDAR both associated with an increased urinary albumin/creatinine ratio. In humans, NMDAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 60 publications
3
86
2
3
Order By: Relevance
“…There are also other examples of a similar link in non‐neuronal cells. In renal podocytes, NMDARs re‐shape cellular foot processes that regulate glomerular filtration 49. To link with the cytoskeletal elements, neuronal NMDARs require post‐synaptic density (PSD) proteins such as PSD‐95 and Yotiao32; both of these are expressed in megakaryocytes31; hence these cells contain the molecules to support such interactions.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other examples of a similar link in non‐neuronal cells. In renal podocytes, NMDARs re‐shape cellular foot processes that regulate glomerular filtration 49. To link with the cytoskeletal elements, neuronal NMDARs require post‐synaptic density (PSD) proteins such as PSD‐95 and Yotiao32; both of these are expressed in megakaryocytes31; hence these cells contain the molecules to support such interactions.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 MPC5 cells were cultured at 33 C (10 U/mL of interferon-c) with 5% CO 2 and were differentiated at 37 C (without interferon-c) with 5% CO2 in RPMI 1640 Dutchmodified medium (Invitrogen, Carlsbad, CA) supplemented with 10% v/v fetal calf serum. Depending on the exact experimental setup, the cultured cells were transfected with miRNA mimics or negative control using Lipofectamine 2000 reagent (Invitrogen, Grand Island, NY).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…16 Previously, these authors found podocyte-specific expression of the small GTPase, rab3A, and its effector, rabphillin 3a; both proteins play an important role in Ca 2ϩ -dependent exocytosis of synaptic vesicles, 17,18 and interestingly, synapses of neurons form a cleft of 20 to 50 nm, which is quite similar to the ϳ40 nm width between foot processes. Earlier electron microscopy studies also showed the presence of "synaptic-like" vesicles in the secondary foot processes of podocytes and the expression of a functional glutamatergic synaptic transmission system, providing a clear hint that podocytes not only exhibit synaptic plasticity but also execute synaptic-like communications.Giardino et al 16 now perform an elegant in vivo study by using rab3A-null mice and pharmacologic antagonists of Nmethyl-D-aspartate (NMDA) receptors to block the glutamatergic signaling system. They observe rab3A deficiency as well as the blockade of NMDA receptors results in increased albuminuria.…”
mentioning
confidence: 96%
“…Giardino et al 16 now perform an elegant in vivo study by using rab3A-null mice and pharmacologic antagonists of Nmethyl-D-aspartate (NMDA) receptors to block the glutamatergic signaling system. They observe rab3A deficiency as well as the blockade of NMDA receptors results in increased albuminuria.…”
mentioning
confidence: 99%